Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.